2021
DOI: 10.1007/s13365-021-00981-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoactivation in the precuneus and posterior cingulate cortex during ambiguous decision making in individuals with HIV

Abstract: People with human immunodeficiency virus (HIV) often have neurocognitive impairment. People with HIV make riskier decisions when the outcome probabilities are known, and have abnormal neural architecture underlying risky decision making. However, ambiguous decision making, when the outcome probabilities are unknown, is more common in daily life, but the neural architecture underlying ambiguous decision making in people with HIV is unknown. Eighteen people with HIV and 20 controls completed a decision making ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Moreover, research on ambiguity aversion could benefit from agent-based simulations (Georgalos 2018 ). Another promising tool to analyze if people are indeed ambiguity-averse is functional magnetic resonance imaging (fMRI) from neuroeconomics (Camerer et al 2007 ; Hall et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on ambiguity aversion could benefit from agent-based simulations (Georgalos 2018 ). Another promising tool to analyze if people are indeed ambiguity-averse is functional magnetic resonance imaging (fMRI) from neuroeconomics (Camerer et al 2007 ; Hall et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It shows the highest metabolic rate at rest, has rich anatomical and functional connections with a wide range of brain regions, and participates in multiple complex cognitive functions, such as visuospatial imagination, episodic memory retrieval, and self-task processing ( Cavanna and Trimble, 2006 ). Damage to this brain region was supported by Hall et al with a task-based functional MRI showing hypoactivation in the precuneus during ambiguous decision-making in PLWH ( Hall et al, 2021 ). In a magnetic resonance spectroscopy study, glutamate reduction in the precuneus of PLWH was reported, and this reduction was associated with information processing speed ( Mohamed et al, 2018 ).…”
Section: Discussionmentioning
confidence: 83%
“…These markers of AD currently include neurodegenerative metrics obtained from MRI (e.g., less GMV) and PET (e.g., abnormal amyloid and tau depositions; Jack et al, 2018 ). Potential future directions might be to combine the Frascati criteria with emerging neuroimaging markers of HAND, including GMV as demonstrated in the present study, as well as functional MRI ( Ances et al, 2009 , Nguchu et al, 2021 , Plessis et al, 2014 , Hall et al, 2021 , Minosse et al, 2021 ) and magnetoencephalography ( Spooner et al, 2020 , Lew et al, 2018 , Wiesman et al, 2018 , Wilson et al, 2017. , Becker et al, 2012a , Becker et al, 2012b ).…”
Section: Discussionmentioning
confidence: 91%